Use of different materials as a carrier for plant growth promoting bacteria - Kankamon Yakanto (2018)
© 2017, Khon Kaen University,Research and Technology Transfer Affairs Division. All rights reserved. Rhizobium and Azospirillum are rhizobacteria which enhance plant growth via nitrogen fixation, nutrients solubilization and hormone production. These activities make them beneficial as microbial bio-fertilizer for legumes and economic crops. In this study, solid-base inoculants i.e. perlite, vermiculite and mixed media were evaluated for their potential use as carriers for Rhizobium CIAT899 and Azospirillum VAs087. Chemical and physical properties of the carrier materials were performed and the population of the two strains was counted. The results revealed that different carrier showed different effect on growth and survival of CIAT899 and VAs087 during 120 days of incubation. Mixed media gave highest number of both strain (108to 109CFU g-1of carriers) while perlite and vermiculite supported survival at only 106-107CFU g-1of carriers during 10 to 30 days of inoculation. On the average the number of CIAT899 was higher in all the carriers than those of VAs087. The number of viable bacteria was decline after reaching the highest number and remained stable, between 104and 106CFU g-1of carriers depended on the type of carrier, after 90 days of incubation. The results indicated that the use of mixed media as a carrier was appropriate for the production of bacterial inoculants.